2023
DOI: 10.1021/acssuschemeng.2c06518
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability of the Globalized Pharmaceutical Supply Chains: The Case of Tenofovir Disoproxil Fumarate

Abstract: Sustained demands for pharmaceutical commodities are continuously created due to economic development and the rapidly aging world population. However, the climate and environmental implications of globalized pharmaceutical manufacturing have not been sufficiently understood to inform the integration of key learnings into sustainability practices. Here, we systematically study the environmental impacts of the pharmaceutical supply chain and identify hotspots through a novel analysis framework. Using the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing the environmental impact of pharmaceutical supply chains, ref. [48] found that reducing the carbon footprint can only be ensured if producers could be incentivized to use environmentally friendly raw materials and purchase renewable energy. Meanwhile, in supply chains, energy footprints could be reduced by a careful selection of materials by allocating resources for the purchase of equipment and personal protection.…”
Section: Environmental Sustainability Of the Supply Chain (Ensc)mentioning
confidence: 99%
“…According to the results of Table 8, it can be seen that with the increase in the size of the problem due to the increase in the number of pharmacies and the demand for different drugs, the costs of the entire hierarchical supply chain network, including location-routing and allocation, have increased. It can also be seen that CPLEX does not have the ability to solve sample problems larger than number (5). This is because the mathematical model is NP-hard.…”
Section: Analysis Of Numerical Examples Of Larger Sizementioning
confidence: 99%